1993
DOI: 10.1111/j.1467-6486.1993.tb00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Leader Style in Strategy and Organizational Performance: An Integrative Framework*

Abstract: By means of reviewing existing literature about the role of leaders in determining organizational strategy, an integrative analytical framework is developed. The framework considers the leader to be key to both the formulation and implementation of strategy. It further identifies factors that moderate the leader's impact on strategy. Hypotheses are presented along with implications for future research regarding the role and impact of leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
14

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 66 publications
2
37
0
14
Order By: Relevance
“…While a strong culture can be a positive asset for a firm creating a sense of unity among its employees, we show that in the M&A context it lacks the needed flexibility to adapt to a new environment. This is in accordance with Nahavandi and Malekzadeh (1993), Buono and Bowditch (1989) and Sorensen (2002). Moreover, we show that a weak organizational culture can change to a strong organizational culture in the context of cross-border M&As.…”
Section: Discussionsupporting
confidence: 68%
“…While a strong culture can be a positive asset for a firm creating a sense of unity among its employees, we show that in the M&A context it lacks the needed flexibility to adapt to a new environment. This is in accordance with Nahavandi and Malekzadeh (1993), Buono and Bowditch (1989) and Sorensen (2002). Moreover, we show that a weak organizational culture can change to a strong organizational culture in the context of cross-border M&As.…”
Section: Discussionsupporting
confidence: 68%
“…Several studies have examined this relationship empirically (Hrebiniak and Snow 1982;Fielder 1986;Thomas 1988;Jacobs and Singell 1993;Nahavandi and Malekzadeh 1993;Costanza 1996). In general, field studies have found that leaders' personality characteristics and behaviors have little effect on organizational productivity as measured by indirect, enterprise-wide financial measures such as profit and return on assets (Costanza 1996;Butler and Cantrell 1997).…”
Section: Leadership and Supervisionmentioning
confidence: 99%
“…In 1993, both Nahavandi and Malekzadeh, and Rajagopalan et al noted that literature focusing on factors impacting decision-making and studies in this literature are both limited in number and have produced mixed results [38,39].…”
Section: Context and Decision-makingmentioning
confidence: 99%